UJI BEBERAPA DOSIS CENDAWAN ENTOMOPATOGEN Cordyceps sp. LOKAL PADA MEDIA BEKATUL PADI terhadap LARVA Oryctes rhinoceros L. di LABORATORIUM - Ramadani, Ferry '; Salbiah, Desita '; Sutikno, Agus ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Oryctes rhinoceros L. grubs is one of the important pest on palm oil. Alternative to control this pest can be use local entomopathogen fungi such as Cordyceps sp. has opportunity as a biological control agent. The experiment was conducted in Plant Pests Laboratory Faculty of Agriculture, University of Riau from Agustus until September 2015. The objective study was to find the better doses of local entomopathogen Cordyceps sp. The treatment tested were doses of local entomopathogen Cordyceps sp. 0 g/cm3, 15 g/cm3, 20 g/cm3, 25 g/cm3 and 30 g/cm3. The experiment used completely randomized design (CRD) with 5 treatments and 4 replications. The result showed that local entomopathogen Cordyceps sp. to control O.rhinoceros L. grubs can cause 87.50% total mortality in dose 25 g/cm3. Â Keywords: Local entomopathogen Cordyceps sp., biological control, Oryctes rhinoceros L.